Análise de aspartato protease (sap) como fator associado à virulência de linhagens de Candida albicans e Candida não-albicans - Silva, Naiara Chaves (2013)
Candida spp. has become in recent decades, major causative agents of invasive infections, responsible for high rates of mortality and morbidity. It is believed that the secreted aspartate protease (Sap) is a factor directly associated with infection exerting decisive role in the pathogenicity of Candida spp. and that the exposure to subinibitory concentrations of antifungals may increase the production of Sap and to select resistant isolates. We analyzed isolates of Candida albicans and Candida non-albicans from cases of hospital infection. We evaluated the protein profile of the isolates of Candida spp. by SDS-PAGE. We evaluated also the susceptibility profile of the isolates against antifungals of use conventional in regimens therapeutics (fluconazole and amphotericin B) and newer antifungals that are not yet part of the hospital routine (voriconazole and caspofungin). It was determined the proteolytic activity qualitative and quantitative of Sap and metabolic activity of isolates of C. albicans and Candida non-albicans grown in the presence and absence of subinhibitory concentrations of fluconazole and amphotericin B. Was established the correlation between the tests and, finally, the expression of the SAP2 gene in C. albicans ATCC 64548 and C. krusei ATCC 6258 was evaluated. 100% of the isolates were susceptible to amphotericin B, voriconazole and caspofungin and 89.9% to fluconazole. Two isolates (7.4%) showed susceptibility dose dependent and one (3.7%) showed resistance to fluconazole. In the qualitative analysis of proteolytic activity, 77.7% of the isolates showed activity. The most isolates of C. albicans (50%) and Candida non-albicans (32%) had moderate proteolytic activity. The addition of fluconazole to culture did not promote significant changes in the proteolytic activity of the isolates patterns, while amphotericin B inhibited the growth of C. glabrata ATCC 90030 and C. krusei ATCC 6258. In quantitative analysis, all isolates were active, being that the highest activity was observed in Candida complex “psilosis” 210 (100%) and the lowest in C. albicans 257 (2.44%). The most of the C. albicans isolates (50%) were classified as weakly proteolytic, while Candida non-albicans (53%) as moderately proteolytic. The presence of antifungals in the culture significantly changed the percentage of substrate degradation of the most of isolates. The greatest difference of percentage was observed in C. lusitaniae 286, which in the presence of ¼ IC90 of amphotericin B increased 13.7x regarding to absence of the drug. The quantitative method of determining the proteolytic activity presented greater sensitivity. 63% of the isolates of Candida albicans showed high metabolic activity and 68% of Candida non-albicans had moderate activity. The higher metabolic activity was observed in C. albicans 120 (61.72%) and lowest in C krusei ATCC 6258 (2.35%). The metabolic activity of the most of the isolates was significantly altered. The major difference of percentages was observed in Candida complex “psilosis” 210, which in the presence of ½ IC50 of fluconazole showed reduction of 8x in the metabolic activity regarding to absence of the drug. There was expression of SAP2 only in C. albicans ATCC 64548, which was significantly reduced in the presence of ¼ IC90 of amphotericin B. The Sap activity may be considered a potential factor associated to virulence, once that the isolate that showed the greatest activity showed susceptibility reduced.